Molecular Mechanisms of the Methionine Sulfoxide Reductase System from Neisseria meningitidis - Sandrine Boschi-Muller (MDPI AG, 2018)
Neisseria meningitidis, an obligate pathogenic bacterium in humans, has acquired different defense mechanisms to detect and fight the oxidative stress generated by the host’s defense during infection. A notable example of such a mechanism is the PilB reducing system, which repairs oxidatively-damaged methionine residues. This review will focus on the catalytic mechanism of the two methionine sulfoxide reductase (MSR) domains of PilB, which represent model enzymes for catalysis of the reduction of a sulfoxide function by thiols through sulfenic acid chemistry. The mechanism of recycling of these MSR domains by various “Trx-like” disulfide oxidoreductases will also be discussed.